Legal Interpretation of Honorariums and Free Services by PPAT in Land Registration - Riki Eri Setyo; Hanif Nur Widhiyanti; Arini Jauharoh (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
This study examines the normative interpretation of the terms “honorarium” and “services without charging fees” under Article 32 of PP No. 24/2016 and Permen ATR/BPN No. 33/2021. Using a normative juridical method with statutory and conceptual approaches, the research explores legal ambiguities in PPAT obligations, especially in digital land services outside the deed-making process. Findings reveal a regulatory vacuum that creates unequal treatment for PPATs and the poor, with unclear implementation boundaries and unjust workloads. The study proposes a normative interpretation model that aligns doctrine with practical conditions, emphasizing distributive and procedural justice. It recommends regulatory reform to classify service types, define reasonable honorariums, and ensure legal protection for all parties in digital land administration.